The colonel who would not repent the Bangladesh war and its unquiet legacy - Tripathi, Salil (Yale University Press, 2016)
Bangladesh was once East Pakistan, the predominantly Muslim nation carved out of the Indian subcontinent when it gained independence from Britain in 1947. As religion alone could not keep East Pakistan and West Pakistan together, Bengali-speaking East Pakistan fought for and achieved liberation in 1971. Coups and assassinations followed, and two decades later it completed its long, tumultuous transition to parliamentary government. Its history is complex and tragic - one of war, natural disaster, starvation, corruption, and political instability.